READING AND HOW TO TEACH IT - Inayah Setiorini; Tono Suwartono; Bowo Prasmoro (KREDO : Jurnal Ilmiah Bahasa dan Sastra, 2022)
Reading is a basic process of constructing meaning in written texts, gaining information, and learning about the wide world. It makes serious problem if someone has difficulties in reading because it is of the most frequent language skill used in daily life. Reading comprehension is the skill to understand what we are reading. In teaching, the main outcome of reading strategies is students have the ability to comprehend reading materials. Reading comprehension is a challenge for students because most of them have various problems in understanding the texts, specifically in unfamiliar words and sentences correlation. This study aims to propose teachers consider that reading comprehension plays a vital role in reading. The study applied library research. Teachers should be sensitive to learn what students’ characteristics are in reading and choose the best strategy in it, build up students’ confidence, provide suitable materials and exercises, and also give more time to explore what students are reading. Further, teachers are expected to put forward comprehension and bring proper strategy to students understand the texts comprehensively. If students can improve their reading comprehension skills, then the purpose of teaching reading has been successfully achieved.